Igitt Ekel als Kultur - Heimerdinger, Timo (bricolage, 2015)
"Yuck!" - we involuntarily disgust ourselves with what could be harmful to us and threatens us. Disgust protects - one might think. But disgust is more. It's not only a physiological response, it's also a cultural achievement. Disgust plays a colorful role in many contexts as interpersonal behaviors and perceptions. In this volume disgust has been ethnographically explored and appears as a cultural player. The authors are looking for places such as hospital wards, public toilets, sailing ships or video booths, they address innards, pranks and rites de passage.